Optimalisasi Supervisi Akademik Untuk Meningkatkan Kualitas Pembelajaran dan Rata-rata Nilai Ujian Nasional SMAN 3 tahun pelajaran 2013/2014 - Yahmin, Moh. (EMPATI, 2016)
The background of this research is the fact that the spirit ofÂ  teaching especially the science teachers of the twelfth grade for national examination (UN) subject is low, so it caused the result of studentsâ achievement. The aim of this research is to describe how academic supervision can increase the teachersâ qualification of teaching especially for the SMA 3 science teachers of theÂ  twelfth Â grade Â for UN subject and also how academic supervision can increase the sum of studentsâ score for the UN subject in SMA 3 for the school year 2013/2014. This research is done in two cycles. The first cycle used the academic supervision with group technic, and the second cycle applied the supervision with individual one. The result of the first cycle indicated that the science teachers of the twelfth grade for UN subject is low. They were in enough category, so it caused the result of tray out of national examination was low too. The sum of that score was 42,51 ( 7,08 everage ). It was still under the result ofÂ  the UN last year.Â Â  The result ofÂ  the second cycle indicated that the science teachers of the twelfth grade for UN subject is high. They were in good category, so it caused the result of UN was high too. The sum of UN especially four 6 science subjects increased. The score was 49,46 (8,24 everage), so it was 0,28 higher than national examination before. The conclusion was that the academic supervision done optimally could increase the teachersâ qualification of teaching especially for the SMA 3 Pati science teachers of the twelfth gradeÂ  for UN subject and also Â academic supervision could increase the sum of studentsâ score for the national examination subject in SMA 3 Pati four the school year 2013/2014. Key words : academic supervision, teaching qualification, optimally, increased.